Green Synthesis of Homogeneous Gold Nanoparticles Using Sargassum spp. Extracts and Their Enhanced Catalytic Activity for Organic Dyes - J. Luis López-Miranda; Gustavo A. Molina; Rodrigo Esparza; Marlen Alexis González-Reyna; Rodolfo Silva; Miriam Estévez (Toxics, 2021)
Sargassum species-based extracts were used to carry out the synthesis of homogeneous gold nanoparticles. Various techniques were used to determine the characteristics and composition of the nanoparticles. The UV-Vis results showed that the 50% water/ethanol extract had the most reducing agents and stabilizers. Therefore, this type of extract was used to synthesize nanoparticles and for their subsequent characterization. Crystallinity and crystal size were evaluated using X-ray diffraction. Size and morphology were analyzed using scanning electron microscopy, showing that the gold nanoparticles were mostly spherical, with a size range of 15–30 nm. The catalytic activity of the gold nanoparticles was evaluated through the degradation of organic dyes: methylene blue, methyl orange, and methyl red. The degradation rates were different, depending on the nature of each dye, the simplest to degrade was methylene blue and methyl red was the most difficult to degrade. The results indicated that the use of Sargassum spp. for the synthesis of gold nanoparticles has potential in the remediation of water that is contaminated with organic dyes. Moreover, given the recent serious environmental and economic problems caused by the overpopulation of Sargassum spp. in the Mexican Caribbean, the findings hold promise for their practical and sustainable use in the synthesis of nanomaterials.